Pengaruh UMKM Kuliner dan Wisata Lokal terhadap Meningkatkan Pertumbuhan Ekonomi di Desa Ranggeh Kecamatan Gondangwetan Kabupaten Pasuruan - Andy Putra; Sugeng Pradikto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Ranggeh Village, located in Gondangwetang District, Pasuruan Regency, has great potential in developing the local economy through the micro, small and medium enterprise (MSME) and tourism sectors. This potential is becoming increasingly prominent along with the development of the culinary industry and natural tourism which is now the main attraction for both local and foreign tourists. The culinary industry in this village is developing rapidly with many food stalls, cafes and restaurants serving typical dishes using local ingredients. This not only satisfies tourists' tastes, but also makes a significant contribution to improving the local economy. Apart from that, the natural beauty and beautiful rural atmosphere in Ranggeh Village is a special attraction for tourists, especially with the presence of natural tourist attractions such as the Suropati baths which offer various unique attractions.The growing tourism sector has encouraged the emergence of various related businesses, such as selling typical village souvenirs, which further increases tourist visits. These two sectors, namely culinary MSMEs and local tourism, have had a large positive impact on the economy of Ranggeh Village by creating new jobs and increasing the income of local people. The development of these two sectors has also led to increased demand for local products, such as food and handicrafts. This article discusses the impact of these two sectors on village economic growth, as well as the challenges and opportunities faced by the community in developing the culinary and tourism MSME sector. With a deeper understanding of these opportunities and challenges, it is hoped that we can maximize the role of these two sectors to improve community welfare and create wider employment opportunities.